On some method for limited services selection. (1st January 2011) - Prusiewicz, Agnieszka; Zięba, Maciej
There are various approaches to solve the problem of services selection according to user request. Usually, ontology-based filtering is used. The problem occurs, if the service can be run a limited number of times and the number of users interested in service execution is higher than the number of possible service executions. In this work we propose the knowledge-based algorithm for limited services selection. It is assumed that knowledge of users is used to determine priorities that are used in a process of services selection. The users' priorities are obtained using clustering and classification methods. The results of testing the accuracy of classifiers for users' priorities determining and the quality of the algorithm for limited services selection are presented.